Fabrication and evaluation of mems thin-film AG/AGCL reference electrode for heavy metal detection - Choo, Joseph Ming Hui (2016)
Aggravating pressures on the world’s water resources are likely to continue due to growth in population, climate changes, and many other challenges. Furthermore, the scarcity of freshwater resources means that not everyone has the access to a reliable and safe water supply. The threats to human health are mainly exposure to common heavy metals such as lead, mercury, cadmium and arsenic. In recent years, research pertaining to development of portable, sensitive and miniaturized chemical sensor, shows great potential since compact chemical sensor can be considered as a potential replacement of conventional centralized testing equipment. Cyclic voltammetry experiment was carried out by continuously scanning potential under varying scan rates using different experimental setups. An all commercial electrodes reference setup was done to create a baseline for this study, and the fabricated reference electrodes were compared against the results of this setup. From the results gathered, the fabricated Ag/AgCl reference electrode showed gratifying results compared to the commercial reference electrode, with minimal shifts in peak potential, suggesting that the proposed MEMS-based chemical sensor, with good controlled fabrication and packaging processes, has very good prospective to be used for electrochemical applications.